Pseudotumor of muscle - focal myositis - Nagabhushanarao, Bhavana V.; Modi, Sailesh; Kumar, Aripaka P.; Chembrolu, Lakshmi S. (International Journal of Research in Medical Sciences, 2024)
Focal myositis is a rare disease, and to date, 250 cases have been reported in literature. It is a benign dysimmune disease of unknown etiology. It is defined as myopathy affecting a single muscle without systemic manifestation with a historically proven inflammatory myositis process. It usually presents as a mass ranging from 1 to 20 centimeters, growing insidiously over weeks to months, and may be painless or tender. Or the growth can be rapid and with a lot of pain and disability. It’s common in lower limbs and rare in facial muscles. It usually regresses spontaneously and does not invade the surrounding structures. In 18% of cases, there may be a relapse. Laboratory studies may show elevated erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP). Creatine kinase (CK) is usually not elevated significantly. Autoantigens are often normal or may be marginally elevated. Magnetic resonance imaging (MRI) is a diagnostic tool of choice and is done with relative ease. Electromyography (EMG) occasionally shows recordable spontaneous and repetitive discharges. Nerve conduction velocity (NCV) may be helpful if nerves are involved. A muscle biopsy usually confirms the diagnosis with specific features. Tumours of muscle and Inflammatory myositis need to be differentiated. Sometimes focal myositis may be associated with immune-mediated inflammatory disease (IMID), neoplasms, radiculopathy, and trauma. Focal myositis is usually self-limiting and benign. It usually responds to NSAID and occasionally may require a short course of steroids, especially in those with elevated ESR and CRP.